The Agency of Sound in the Light of Acoustic Ecology and Timothy Morton’s Ecology without Nature Concept - Degórski, Przemysław (Sensus Historiae, 2020)
The article raises the issue of Raymond Murray Schafer’s soundscape, its agency and its anthropocentric perspective. The author of the article juxtaposes the acoustic ecology and Timothy Morton’s ecology without Nature and notes the first- and thirdperson relationship forming between the human and the sound in Schafer’s model. The way to overcome the distance seems to be adopting the zero-person perspective and applying the hyperobject model for describing the correlations between humans and non-humans.